Prostatic Stromal Hyperplasia with Atypia - Ryan C. Hutchinson; Kevin J. Wu; John C. Cheville; David D. Thiel (Case Reports in Urology)
Prostatic stromal hyperplasia with atypia (PSHA) is a rare histologic finding diagnosed incidentally on prostate biopsies, transurethral resection specimens, and radical prostatectomy specimens. PSHA has a bizarre histologic appearance and these lesions often raise concern for sarcoma; however, their clinical course is indolent and does not include extraprostatic progression. We discuss a case of PHSA discovered on prostate biopsy performed for an abnormal digital rectal examination and review the literature on this rare pathologic finding.